2020
DOI: 10.1007/s00431-020-03649-w
|View full text |Cite
|
Sign up to set email alerts
|

Application of PECARN rules would significantly decrease CT rates in a Dutch cohort of children with minor traumatic head injuries

Abstract: The aim of this study was to determine the potential impact of the Pediatric Emergency Care Applied Research Network (PECARN) rules on the CT rate in a large paediatric minor traumatic head injury (MTHI) cohort and compare this with current national Dutch guidelines. This was a planned sub-study of a prospective multicentre observational study that enrolled 1006 children younger than 18 years with MTHI. We calculated the number of recommended CT scans and described trauma-related CT scan abnormalities. The PEC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…4,7 The development of guidelines for the utilization of head CT for the evaluation of TBI is important and has likely reduced the number of tests ordered. 8 Nonetheless, limitations of these studies should be recognized when used clinically. For instance, one of the more robust studies to produce head CT guidelines excluded patients with "trivial injury mechanisms," evidence of penetrating trauma, known brain tumor, a neurological condition that would complicate assessment, or for patients with concerns for abusive head trauma.…”
Section: Discussionmentioning
confidence: 99%
“…4,7 The development of guidelines for the utilization of head CT for the evaluation of TBI is important and has likely reduced the number of tests ordered. 8 Nonetheless, limitations of these studies should be recognized when used clinically. For instance, one of the more robust studies to produce head CT guidelines excluded patients with "trivial injury mechanisms," evidence of penetrating trauma, known brain tumor, a neurological condition that would complicate assessment, or for patients with concerns for abusive head trauma.…”
Section: Discussionmentioning
confidence: 99%
“…Our study performed in an Italian pediatric ED confirmed the efficacy and safety of the PR in detecting the presence of ciTBI in patients with MHI, reducing radiological investigations and exposure to ionizing radiations. In literature, different authors proposed clinical algorithms to optimize management of pediatric patients with MHI but the PR seems to have the best methodological quality [6][7][8][9][10][11][12][13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…It was subsequently validated in other populations and settings [7,8]. PR is currently used in many countries for the ED management of children with MHI [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Yet, it would be preferable to provide clinicians better tools to make a solid choice between observation and CT scan in this large group of children. Namely up to 50% of young children under 6 years of age with MTHI classify as IR [ 22 ]. Literature shows there are several subjective factors guiding the decision of clinicians, for example clinical experience of the clinician [ 7 ] and parental preference [ 8 ].…”
Section: Discussionmentioning
confidence: 99%